Long-term outcomes after cytoreductive surgery and HIPEC for morcellated uterine leiomyosarcoma; A case series - Maya Yasukawa; Louis A. Dainty; Paul H. Sugarbaker (Elsevier, 2021)
Uterine leiomyosarcoma (uLMS) is a rare aggressive malignant mesenchymal tumor with high risk of recurrence and poor prognosis regardless of stage. It is often diagnosed postoperatively following myomectomy, hysterectomy or supracervical hysterectomy for presumed benign disease. Primary surgery at the diagnosis of uLMS is considered to affect outcomes. If the tumor was morcellated, the oncologist will encounter special problems that require knowledgeable management of peritoneal metastases. We previously reported that six patients who successfully underwent cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) plus early postoperative intraperitoneal chemotherapy (EPIC) to manage the disease dissemination that must occur following morcellation. This is a study for long-term outcome of these patients. Six patients were treated with an absence of grade IV adverse events and no mortality. The median Peritoneal Cancer Index (PCI) was 18 and complete cytoreduction without peritoneal metastases visualized within the operative field at the completion of the surgical procedure (CC-0) was achieved in all patients. One patient was diagnosed leiomyomatosis peritonealis postoperatively. Among five patients who were confirmed uterine leiomyosarcoma, the 3-year overall survival was 40.0% and 5-year overall survival was 20.0% with the median follow-up of 18 months (range 5-73 months). The patient with PCI 0 at the time of CRS showed no evidence of disease (NED) at 73 months. We believe that prophylactic CRS contributed her favorable outcome. Therapeutic options for patients with uLMS post-morcellation are limited. Currently, CRS and HIPEC plus EPIC followed by adjuvant systemic chemotherapy may be considered an option for treatment. Further studies in a larger number of patients are needed.